Pore-size changes and responses of kaolinite with different structures subject to consolidation and shearing - Yu, Chun Ying; Chow, Jun Kang; Wang, Yu-Hsing (Engineering geology, 2016)
In this paper, the responses of kaolinite samples with two different soil structures, i.e., unwashed and pH7.8 samples, under 1-D consolidation, isotropic loading–unloading and triaxial shearing are examined. The focus is on the associated changes in the pore-size distribution. During isotropic consolidation, the unwashed sample, with an open, aggregated and flocculated structure, exhibits higher compressibility than the pH7.8 sample, which has a densely packed aggregated structure. The associated deformation in both samples primarily arises from the compression of the large inter-aggregate pores, which are not controlled by the suppression of the electrical double layer, and the intra-aggregate pores remain almost unchanged during consolidation. Similar behavior is observed in clay samples with different structures during 1-D consolidation and triaxial shearing that only the inter-aggregate pores are affected and the intra-aggregate pores stay almost the same. All of these findings suggest that the mechanical responses of kaolinite clay depend on aggregate-to-aggregate interactions rather than on particle-to-particle interactions. The aggregates of kaolinite clay can be considered analogous to sand particles. •Consolidation and shearing involves the inter-aggregate pores of kaolinites.•Mechanical responses of kaolinite depend on aggregate-to-aggregate interactions.•The aggregates of kaolinite can be considered analogous to sand particles.